Salvia miltiorrhiza in thorax and abdomainal organ fibrosis: A review of its pharmacology - Yang, Zhao; Qi, Jingshu; Ping, Dabing; Sun, Xin; Tao, Yanyan; Liu, Chenghai; Peng, Yuan (Frontiers in Pharmacology, 2022)
Organ fibrosis is a common pathological change that finally results in organ failure, which involves the destruction of parenchyma cells, the activation of mesenchymal cells and the imbalance of immunological cells. In recent years, although some breakthroughs have been made in understanding the pathogenesis and therapeutics of organ fibrosis, no registered drugs could directly target the fibrotic process, which constitutes a major biomedical challenge. Salvia miltiorrhiza (SM) is a well-known medicinal plant in China, which has been widely applied because of its pharmacological effects on anti-oxidative, anti-myocardial infarction, anti-fibrotic, anti-inflammatory, and anti-neoplastic properties. Accumulated evidence suggested that SM played critical roles against organ fibrosis in vivo and in vitro experiments by its multiple biological compounds. In this review, we discussed the recent advances on the phytochemistry and pharmacological mechanisms of SM and its active ingredients in liver, lung, kidney, and heart fibrosis, which might help to promote the treatment of fibrotic diseases in thorax and abdomainal viscera in clinic.